ANALISA KEPUASAN PENGUNJUNG MENGGUNAKAN METODE DECISION TREE DI PERKAMPUNGAN BUDAYA BETAWI SETU BABAKAN JAKARTA - Kudiantoro Widianto; Achmad Rifai; Mutiara Nur Pratiwi (Jurnal Mantik Penusa)
Tourist attraction managers in Jakarta make various efforts to win the competition, among others by increasing tourist visitor satisfaction. One of the attractions in Jakarta is Setu Babakan which is one of the attractive tourist attractions for tourists who want to enjoy the typical atmosphere of the countryside or witness native Betawi culture firsthand. In Setu Babakan, visitors can see natural scenery, enjoy typical Betawi culinary which is relatively cheap, and watch Betawi cultural arts performances. In addition, the manager of Setu Babakan also provides various facilities such as toilets, places of worship, children's playgrounds, and others to support visitors' activities. To visit Setu Babakan, there are many public vehicles that pass through this village and the cost is quite cheap. This study aims to analyze the visitors' satisfaction of Setu Babakan by using the attributes of cost, facilities, accessibility, and service. Researchers use the decision tree method C4.5 algorithm. From the decision tree image processed by RapidMiner it can be seen that the factors of visitor satisfaction are facilities and accessibility. After that the trial was performed on the dataset 3 times from the questionnaire data on 50 visitors obtained an accuracy of 100%. The classification results with the C4.5 algorithm of 100% are considered appropriate to be used to measure the level of visitor satisfaction with costs, facilities, accessibility, and service.